THU0403 Serum levels of macrophage migration inhibitory factor and interleukin-1 family cytokines are elevated in systemic sclerosis. (12th June 2018) - Lin, E.; Vincent, F.; Harris, J.; Kandane-Rathnayake, R.; Ngian, G.-S.; Sahhar, J.; Morand, E.; Lang, T.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune connective tissue disorder, the pathogenesis of which remains unknown. Recent evidence suggests dysregulation of the innate immune system, particularly interleukin-(IL)−1 family cytokines. Given the emerging role of macrophage migration inhibitory factor (MIF) in pathways of IL-1 family cytokine secretion, the role of MIF, IL-1α, IL-1β and IL-18 in SSc is of interest. Objectives: To examine associations between MIF and IL-1 cytokines (IL-1α, IL-1β, IL-18), in SSc, and associations with clinical features. Methods: 115 SSc patients (2013 ACR/EULAR criteria) attending Monash Scleroderma Clinic and 52 healthy controls were recruited between August 2015 and August 2017. Serum MIF, IL-1α, IL-1β and IL-18 levels were quantified using ELISA and analysed alongside concurrent clinical and laboratory data from the Australian Scleroderma Cohort Study database Results: Compared to controls, SSc patients had significantly elevated serum MIF and IL-18 (figure 1). A weak positive correlation was observed between MIF and SScHAQ score (R=0.2107, p=0.0437) which was stronger in the diffuse cutaneous (dcSSc) subgroup (R=0.457, p=0.0373). Patients with elevated IL-18 levels were more likely to have active disease (EUSTAR score ≥3) however IL-18 was lower in patients with pulp atrophy and sclerodactyly. IL-1β was elevated in dcSSc patients with pulmonary fibrosis and correlated with mRSS (R=0.213, p=0.0254) in all SSc patients. IL-1α was elevated in patients with joint contractures and pulp atrophy. Positive correlations were found between concentrations of MIF and both IL-1α and IL-1β. However, there was no significant correlation between MIF and IL-18. Conclusions: MIF and IL-18 were significantly elevated in SSc compared to health controls, and IL-1 family cytokines were variably associated with clinical manifestations of SSc. A relationship between MIF and IL-1β was confirmed. Further investigation into the roles of MIF and IL-1 family cytokines in SSc is justified. References: [1] Zhang L, Yan JW, Wang YJ, Wan YN, Wang BX, Tao JH, et al. Association of interleukin 1 family with systemic sclerosis. Inflammation2014;37(4):1213–20. [2] van Bon L, Cossu M, Radstake TR. An update on an immune system that goes awry in systemic sclerosis. Curr Opin Rheumatol2011;23(6):505–10. Disclosure of Interest: None declared